Antibiotic prophylaxis for head and neck cancer surgery - A. O. Guz; D. M. Fatkullin; A. V. Garev; A. S. Zakharov; M. I. Sokolova; A. P. Alekseeva (Опухоли головы и шеи, 2020)
This review analyzes the research data concerning the problem of antibiotic prophylaxis (ABP) of wound infections after various surgeries for head and neck tumors. In patients with clean wounds, ABP should be used in exceptional cases only (for example, if the patient has any risk factors), otherwise it should be avoided. A short ABP course is recommended for patients with clean-contaminated wounds; however highrisk patients may require a prolonged course. There is some evidence of ABP efficacy in patients with non-contaminated wounds after cervical lymphadenectomy. When choosing a drug for ABP, a doctor should consider the site of surgery and the risk of wound contamination. The optimal drugs after head and neck surgeries include first- and second-generation cephalosporins, ampicillin in combination with sulbactam, metronidazole, and clindamycin. First- and second-generation cephalosporins in combination with metronidazole are preferable, but if the wound is infected with gram-positive bacteria, it is necessary to use clindamycin monotherapy. Reconstructive surgeries with a free flap require a short course of ABP with one of the following combinations: cefazolin + metronidazole, cefuroxime + metronidazole, or ampicillin + sulbactam; if the patient is allergic to beta-lactams, clindamycin can be used. Despite the availability of standard ABP regimens, a surgeon must apply a tailored approach when choosing an ABP regimen for each patient, taking into account risk factors and the volume of surgery.